Towards a Typology of Inquiry-Based Learning Syntax in Science Education: A Systematic Literature Review (2016–2025) - Rifaul Annisa; Nanang Winarno; Diana Rochintaniawati; Taufik Rahman; Jefelson M. Paltep (FKIP Universitas Lampung, 2026)
This study reviewed 41 articles published between 2016 and 2025 that addressed the implementation of Inquiry-Based Learning (IBL) in science education. While several previous studies have discussed inquiry learning models and their relevance to various science disciplines, few have systematically examined the variation of IBL syntax across models and how its implementation aligns with educational contexts and developmental levels. The purpose of this study is to map and analyze the use of IBL syntax across models, learning environments, educational levels, and technology integration, thereby providing a clearer framework for teachers and curriculum developers. This study employed a systematic literature review method. Article characteristics were described based on year of publication, publication type, research method, country of origin, educational level, and scientific content. The analysis revealed that IBL syntax varies depending on context, learning model, educational level, and technology use. In elementary school settings, inquiry activities generally focus on initial engagement, observation, and simple exploration. At the secondary school level, IBL emphasizes more complex investigative skills, data analysis, and interpretation. In secondary and higher education, syntax often encompasses elaboration, evaluation, reflection, collaboration, and technology-supported activities such as virtual laboratories, simulations, or project-based investigations. Based on these findings, a practical typology of IBL syntax is proposed that organizes instructional steps by frequency of use, learning objectives, and alignment with students' developmental stages. This typology can serve as a methodological framework to guide teachers and curriculum developers in adapting IBL models to classroom contexts and student characteristics. This study provides theoretical insights and practical guidance for designing structured and context-sensitive inquiry activities. Future research is recommended to explore underutilized syntax, validate the proposed typology in classroom settings, and examine strategies to support teacher readiness and resource availability, thereby encouraging a more systematic and context-appropriate implementation of inquiry-based learning in science education. Keywords: systematic literature review, science education, learning syntax, and inquiry-based learning.